Evaluating the Implementation of Green Economy Policies in Addressing Deforestation to Support the Achievement of the Sustainable Development Goals (SDGs) in Indonesia - Meisya Tantri Girsang; Ali Maksum (Journal of Government and Politics (JGOP), 2026)
The green economy has emerged as a strategic policy framework for promoting sustainable development and accelerating the achievement of the Sustainable Development Goals (SDGs) in Indonesia. Despite the adoption of various green economy initiatives, deforestation remains a persistent environmental challenge, indicating a discrepancy between policy objectives and implementation outcomes. This study evaluates the effectiveness of green economy policies in addressing deforestation and examines their contribution to achieving the SDGs in Indonesia. A qualitative research design was employed using a systematic literature review of peer-reviewed journal articles, government publications, reports from international organizations, and official statistical data. The collected data were analyzed through thematic content analysis, guided by Ecological Modernization Theory (EMT) to examine the relationships among environmental governance, institutional reform, and forest conservation. The findings indicate that Indonesia has made measurable progress in reducing net deforestation through forest rehabilitation and restoration programmes. However, independent satellite-based monitoring by Global Forest Watch shows that forest cover loss continues in several regions, suggesting that current green economy policies have been more effective in mitigating the impacts of deforestation than in addressing its underlying drivers. The study identifies institutional fragmentation, inconsistent law enforcement, competing land-use interests, and limited governance capacity as the principal barriers to effective policy implementation. By integrating Ecological Modernization Theory with policy implementation analysis and complementary deforestation datasets from the Ministry of Environment and Forestry (KLHK) and Global Forest Watch, this study provides a more comprehensive framework for evaluating green economy policies and demonstrates that strengthening institutional coordination, governance effectiveness, and stakeholder collaboration is essential for advancing SDG 13 (Climate Action) and SDG 15 (Life on Land) in Indonesia